ANALISIS MOTIVASI PEGAWAI PADA KANTOR BADAN PEMBERDAYAAN MASYARAKAT DAN PEMERINTAHAN DESA KABUPATEN MAMUJU UTARA - Aripin, M. Taqdir (Katalogis, 2016)
Objective to analyze motivation office worker Community Empowerment Board and Village Government of North Mamuju regency. This type of research is qualitative. The method used is the collection of the data include: interviews, direct observation, and Documentation. Based on the research results Analysis Motivation Employees At Community Empowerment Board and Village Government Mamuju Utara The better, because in view of the employees are already motivated to work properly serve the public because the existence of a desire to meet their needs achievers to gain recognition both from employers or fellow colleagues and daeri inside peagawai itself. Similarly, the indicators The need to actualize themselves, some employees are motivated to work and gain knowledge to get a job promotion higher reversed his service as a public servant, but for the majority of employees need to be social not a motivation to improve performance, as well as the need for physiology and the need for security , has been running well because so long cooperative relationship has been harmonized to achieve tujauan along with an increase in quality of public services.